Metal-free cascade synthesis of unsymmetrical 2-aminopyrimidines from imidazolate enaminones. Issue 39 (14th July 2021) - Cui, Xue; Ma, Jianting; Zeng, Tingting; Xu, Junyu; Li, Youbin; Wang, Xuesong
Abstract : A convenient metal-free synthesis of unsymmetrical 2-aminopyrimidines from imidazolate enaminones has been developed. Abstract : A convenient metal-free synthesis of unsymmetrical 2-aminopyrimidines from imidazolate enaminones has been developed. In this procedure, various structural 2-aminopyrimidines, as well as 4, 5-dihydroisoxazol-5-ols and pyrazoles were synthesized in moderate to excellent yields. A plausible mechanism was also proposed for the cascade reaction. This method represents an effective strategy towards the synthesis of unsymmetrical 2-aminopyrimidines.